Learning Genotyping and Cell Culture Techniques to Perform Experiments to Study Cardiovascular Calcification - Ramanathan, Rekha (Journal of Student Research, 2023)
The St. Hilaire Lab at the University of Pittsburgh studies important cardiovascular diseases such as Calcific Aortic Valve Disease (CAVD), Arterial Calcification due to Deficiency of CD73 (ACDC) and Medial Arterial Calcification (MAC). The similarity between all these conditions is the calcification of cells, which leads to the main research question of the lab: how and why does a healthy cell transition into an osteogenic cell? To determine why a healthy cell becomes calcified, we perform experiments using both in vivo and in vitro environments. However, to begin in vitro experiments that involve valuable human cells, basic techniques in cell culture such as plating and splitting are needed, and in vivo experiments require knowing the genotype of the animals being used. With these fundamental techniques, biochemical analysis such as qPCR, western blots and staining can be performed in order to help answer research questions that pertain to the lab.